High‐resolution synchrotron X‐ray fluorescence investigation of calcite coralloid speleothems: Elemental incorporation and their potential as environmental archives. Issue 7 (28th June 2019) - Vanghi, Valentina; Borsato, Andrea; Frisia, Silvia; Howard, Daryl L.; Gloy, Gertruida; Hellstrom, John; Bajo, Petra
Abstract: Synchrotron high‐resolution and micro‐X‐ray fluorescence elemental mapping of two coeval coralloid speleothems from Lamalunga Cave (Italy) are complemented with petrographic, morphological and microstratigraphic studies. The importance of these speleothems relies on their direct and indirect association with a complete Neanderthal skeleton ('Altamura Man') found inside the cave. The coralloids grew discontinuously between 64·6 ka and the Holocene and reveal exceptionally high concentrations of Mg, Sr and Si, particularly on convex surfaces, where evaporation is more intense. The incorporation of trace elements depends on several factors including location, shape and geometrical evolution during their growth, as well as climate and environmental parameters. This resulted in calcite precipitation with Sr compositions from 100 to 1200 ppm and an average concentration of 7000 ppm Mg. An unusually high Si content (up to 16%) is possibly derived from volcanic ash transported as particulate and in solution inside the cave. The most common fabrics observed consist of non‐fluorescent elongated columnar calcite forming clean isopachous bands and fluorescent fibre‐like crystals associated with laminated, lenticular bands high in Sr, Mg and Si. Variability in Sr, Mg and Si concentrations appears to induce fabric changes in the coralloids. Elongation and lattice distortion of the crystals was found to coincide with high Mg concentrations. The transition from compact elongated to open to fibre‐like, is here interpreted as due to high concentrations of Si and Sr, which are preferentially incorporated in the speleothem at crystal boundaries and intra‐laminae. It is here inferred that coralloid fabric changes and their elemental content potentially record local rainfall variations through time, with the clean compact calcite marking high infiltration and open fibre‐like and micrite fabrics recording dry periods.